PERANCANGAN SISTEM INVETORY BARANGSEKOLAH DASARNEGERI 1 TAMAN FAJAR BERBASIS DESKTOP - Wulandari, Ika Arthalia; Farahhusna, Asa; Luthvi Azizah, Alif (Jurnal Ilmiah Sistem Informasi (JISI), 2024)
Inventory of goods is the processing of data on goods in a place. There are also benefits of inventory in educational institutions, namely providing data and information to determine needs and providing data and information for submitting assistance for procurement of goods in the following school year. The absence of data collection of goods at State Elementary Schools 1 Taman Fajar means that they are not recorded, so they cannot provide data and information for requests for school assistance; the absence of data collection of school goods also causes many losses and damages of goods. This problem is the primary reference for creating a desktop-based inventory system. With an inventory system of goods at UPTD SD NEGERI 1 TAMAN FAJAR, it is expected to be more efficient in managing resources and improving services to students, teachers, and school staff.